KENYAMANAN INAP AT CAPSULE HOSTEL SEBAGAI DESAIN COMPACT - Ahmad Muzzayin Dina Wari; Setiamurti Rahardjo; Dea Aulia Widyaevan (Universitas Trisakti, 2020)
AbstractThe increasing number of millennial travelers has affected the growth of backpacker accommodations in Bandung, especially those which are built in a form of capsules. Located at the city center of Bandung, “Inap at Capsule Hostel” has many facilities, all of which are installed inside the capsules and make the design compact. Although all of those facilities are dimensionally accommodated, the anthropometric comfort of the capsule is still questionable since there are spaces required for body movements. With combining the qualitative method through experiencing the capsule’s interior directly and the quantitative method through analyzing reviews from booking websites with the instrument word cloud text analysis, it is found that the compact design of Inap at Capsule Hostel still represents the anthropometric comfort regardless its limited dimension. Nevertheless, rearrangement of some lighting facilities and materials inside the capsules is suggested to improve the quality of the spatial comfort. AbstrakMeningkatnya wisatawan milenial menjadi salah satu faktor pendorong berkembangnya penginapan backpacker berbentuk kapsul di kota Bandung. Inap at Capsule Hostel yang terletak di pusat kota Bandung memiliki lima belas fasilitas yang semuanya terletak di dalam unit kapsulnya dan membuat desainnya padat. Meskipun seluruh fasilitas tersebut dapat tertampung secara dimensi, tapi hal ini belum tentu sejalan dengan kenyamanan kapsul ini saat digunakan karena tubuh manusia memiliki aktivitas gerak yang membutuhkan ruang tambahan. Dengan memadukan metode kualitatif melalui pengalaman ruang secara langsung dan metode kuantitatif melalui olahan data review dari situs pemesanan akomodasi dengan word cloud text analysis, ternyata ditemukan bahwa unit yang padat pada Inap at Capsule Hostel masih nyaman digunakan meski secara dimensi terhitung sempit bagi ruang gerak manusia. Meskipun demikian, disarankan adanya penataan ulang beberapa fasilitas pencahayaan serta penggunaan material untuk meningkatkan kualitas kenyamanan ruangnya.